Work-related stress and associated factors among health professionals in zone 1, Afar region, Ethiopia - Sadat Mohammed Yesuf; Behailu Tariku Derseh; Daniel Girma; Tadesse Mamo Dejene (Heliyon, 2022)
Background: In developing nations like Ethiopia, the number of people suffering from work-related stress is rising at an alarming rate, and it is becoming a public health concerns. Objectives: The goal of this study is to examine work-related stress and associated factors among health care professionals working in governmental and commercial health care facilities in Zone 1 of Ethiopia's Afar region in 2021. Methods: A comparative cross-sectional survey was done among 435 health professionals working at government and commercial health facilities in Zone 1, Afar, between April 1 and May 30, 2021. Self-administered structured questionnaires were employed to collect data, and multistage sampling was used to reach out to the study participants. To assess occupational stress, the Perceived Stress Scale was employed (PSS-10). To see if there is a difference in stress levels between government and private health practitioners, a chi-square test of independence was used. In multivariable logistic regression, a statistically significant relationship was found with a p-value of less than 0.05. Results: This study had a total of 435 participants, with a 96.7 percent response rate. Work-related stress was reported by 67.5 percent of government and 47.2 percent of private health professionals, respectively, and overall stress was reported by 57.5 percent. A chi-square test revealed a significant difference in stress between health professionals working in government and private facilities, X2 (1, N = 435) = 18.19, p < 0.001. A monthly income of 4001–5500 ETB, being a male professional, working 40 h per week, having support and assistance at work, job satisfaction, and uncomfortable room temperature were all linked to work-related stress. Conclusion: Health practitioners in government facilities experienced more stress than those in the private sector. Moreover, the level of work-related stress was high. Effective programs and protocols are needed to maintain a healthy working environment.